Community Transmission of Severe Acute Respiratory Syndrome Coronavirus 2, Shenzhen, China, 2020 - Liu, Jiaye; Liao, Xuejiao; Qian, Shen; Yuan, Jing; Wang, Fuxiang; Liu, Yingxia; Wang, Zhaoqin; Wang, Fu-Sheng; Liu, Lei; Zhang, Zheng (Emerging infectious diseases, 2020)
Since early January 2020, after the outbreak of coronavirus infection in Wuhan, China, ≈365 confirmed cases have been reported in Shenzhen, China. The mode of community and intrafamily transmission is threatening residents in Shenzhen. Strategies to strengthen prevention and interruption of these transmissions should be urgently addressed.